2018
DOI: 10.1159/000489954
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of DNA Methylation and Gene Expression Identify a Three-Gene Signature for Predicting Prognosis in Lower-Grade Gliomas

Abstract: Background/Aims: In the current study, we performed an integrated analysis of genome-wide methylation and gene expression data to find novel prognostic genes for lower-grade gliomas (LGGs). Methods: First, TCGA methylation data were used to identify prognostic genes associated with promoter methylation. Second, candidate genes that were stably regulated by promoter methylation were explored. Third, Cox proportional hazards regression analysis was used to generate a prognostic signature, and the signature genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Lower-grade gliomas (LGG) constitute the prevalent primary malignances of the central nervous system, demonstrating great intrinsic heterogeneity in terms of their biological behavior (Ostrom et al, 2013;Zeng et al, 2018). So far, maximum surgical resection combined with postoperative radiotherapy and chemotherapy is the standard treatment for LGG.…”
Section: Introductionmentioning
confidence: 99%
“…Lower-grade gliomas (LGG) constitute the prevalent primary malignances of the central nervous system, demonstrating great intrinsic heterogeneity in terms of their biological behavior (Ostrom et al, 2013;Zeng et al, 2018). So far, maximum surgical resection combined with postoperative radiotherapy and chemotherapy is the standard treatment for LGG.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,Chen X.P et al reported a model containing 3 genes(EMP3、GSX2、EMILIN3) based on integrative analysis of DNA methylation and gene expression in TCGA dataset (Zeng et al 2018).Chuang Zhang et al also reported a 4-gene(EMP3、GNG12、KIF2C、IFI44) prognostic signature based on genes encodes by chr1p/19q (Zhang et al 2019a). To compare the prognostic values of our prognostic signature and their model,we performed time-dependent ROC curve analysis in our model and other models based on the risk score calculated by the regression coefficients which obtained by themselves and the expression level of members in their signature showed in both TCGA and CGGA dataset.…”
Section: A Comparison Between Our and Other Modelsmentioning
confidence: 99%
“…12,14 Genetic mutations can affect gene expression by means of aberrant transcription, epigenetic regulation, and cell signaling and gene dosage effects. 15 Gene expression profiles have been shown to exhibit the underlying characteristics of cancer, and are typically used to provide prognostic information for LUAD patients [16][17][18] and design new drug targets 19 however, incorporating gene expression-based methods into clinical practice has been met with difficulty, including overfitting, interpatient histologic heterogeneity, intratumoral heterogeneity, and a lack of accounting for existing clinical variables. 20,21 Moreover, the limitations of individual biomarkers mean that they cannot be used as reliable classifiers.…”
Section: Introductionmentioning
confidence: 99%